Rearing and estimation of life-cycle parameters of the tubicifid worm Branchiura sowerbyi: Application to ecotoxicity testing. - Ducrot, V., A.R.R. Pery, H. Queau, R. Mons, M. Lafont & J. Garric (Science of the Total Environment, 2007)
This paper provides original collection, acclimatizing, rearing and toxicity test methods for the freshwater worm Branchiura sowerbyi, an alternative species to Tubifex tubifex for ecotoxicity evaluation of sediments. Influence of the substrate, type of food, and feeding level on individual performances was assessed in short-term tests, in order to set up optimal culture and test conditions. Low-size particles and high organic matter content favoured the growth and reproduction of B. sowerbyi. The relative contribution of sediments and fish food to the individual food intake was assessed using a foraging efficiency model based upon the dynamic energy budget theory. Individual performances were optimal when the substrate plus fish food provided the energy equivalent to 5 mg Tetramin ® per worm per day, which is the ad libitum food level for adults at 21 °C. The life-cycle of the worm was fully characterized using a life-cycle test conducted under the previously defined optimal conditions. Hatching rates were low (32%), whereas newborn and juveniles exhibited high survival (N80%) and growth (2.4 mg/day in juveniles) rates. Age at puberty was low (60 days) when compared to the maximal life span (1100 days) as predicted using a Weibull model. Adults reproduced every other month with a constant fecundity (0.16 cocoon/worm/day). The mean values of the life-cycle parameters and their variability and reproducibility among laboratory studies were discussed in order to identify relevant endpoints to be used in ecotoxicity tests. Survival, juvenile growth, and fecundity may constitute suitable test endpoints, whereas hatching rate and adult growth should not be used as endpoints in B. sowerbyi.